Data Flows Routing in Multiservice Networks Based on Quality of Service Requirements - N. I. Listopad; L. O. Bouka (Цифровая трансформация)
The article deals with the problem of data flows routing in multiservice networks. It is shown, that using of different values of the weight and cost coefficients allows to realize the multi-criteria search for the optimum route taking into account the limitations for each QoS-setting individually as well as with the composite metric r requirements for the shortest path searching.